Advanced peripheral microvascular endothelial dysfunction and polyvascular disease in patients with high cardiovascular risk. Issue 5 (May 2016) - Maeda, Hirofumi; Sugiyama, Seigo; Jinnouchi, Hideaki; Matsuzawa, Yasushi; Fujisue, Koichiro; Hirata, Yoshihiro; Kurokawa, Hirofumi; Ohba, Keisuke; Matsubara, Junichi; Nozaki, Toshimitsu; Konishi, Masaaki; Akiyama, Eiichi; et al.
Abstract: Background: Polyvascular disease (PolyVD) refers to the coexistence of coronary artery disease (CAD), peripheral arterial disease (PAD), and/or cerebrovascular disease (CVD), and carries a high risk of cardiovascular mortality. Endothelial dysfunction plays a crucial role in cardiovascular pathophysiology. This study investigated the association between PolyVD and the presence of microvascular endothelial dysfunction. Methods: Consecutive stable patients ( n = 533) with diabetes mellitus and/or multiple cardiovascular risk factors were enrolled. Peripheral microvascular endothelial function in the finger microvasculature was assessed using the reactive hyperemia peripheral arterial tonometry index (RHI), and ankle-brachial index was measured for diagnosis of lower-extremity PAD prior to coronary angiography. Diagnosis of CVD was based on clinical symptoms, carotid ultrasound, and magnetic resonance imaging. PolyVD was defined as two or more coexisting vascular diseases from CAD, lower-extremity PAD, and CVD. Results: Natural logarithmic transformations of RHI (Ln-RHI) were significantly attenuated in 93 patients with PolyVD (0.44 ± 0.20) compared with those in 440 patients without PolyVD (0.56 ± 0.19; p < 0.001) or in 299 patients with a single vascular disease (0.54 ± 0.19; p < 0.001). There was an independent correlation between Ln-RHI (per 0.1) and the presence of PolyVD in all high-risk patients [odds ratio (OR): 0.724; 95% confidence interval (CI): 0.610–0.859; p < 0.001] and one or more vascular diseases (OR: 0.724; 95% CI: 0.605–0.867, p < 0.001). Receiver-operating characteristics curve analysis showed that Ln-RHI correlated significantly with PolyVD (area under the curve, 0.682, 95% CI: 0.625–0.740, p < 0.001). The optimum cut-off point of Ln-RHI for the existence of PolyVD was 0.479. Conclusions: Microvascular endothelial dysfunction is significantly associated with the presence of PolyVD. Severe impairment of endothelial function in peripheral microvasculature may be an important pathophysiological component of PolyVD.